2021
DOI: 10.1111/acem.14213
|View full text |Cite
|
Sign up to set email alerts
|

Self‐obtained vaginal swabs are not inferior to provider‐performed endocervical sampling for emergency department diagnosis of Neisseria gonorrhoeae and Chlamydia trachomatis

Abstract: Objective Provider‐performed endocervical sampling (PPES) in the diagnosis of Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) may be difficult to perform in a busy emergency department (ED) due to patient preference, availability of the pelvic examination room, or provider availability. Our objective was to assess if self‐obtained vaginal swabs (SOVS) were noninferior to PPES in the ED diagnosis of NG/CT using a rapid nucleic acid amplification test (NAAT). Methods We conducted a prospective observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…Eighty per cent of studies (36 of 45) detected newly diagnosed positive CT/GC infections and 42.2% of studies (19 of 45) measured test accuracy 16 17 20 22–55. Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53. We excluded four studies where reference test was unclear/not reported 22 31–33…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighty per cent of studies (36 of 45) detected newly diagnosed positive CT/GC infections and 42.2% of studies (19 of 45) measured test accuracy 16 17 20 22–55. Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53. We excluded four studies where reference test was unclear/not reported 22 31–33…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53. We excluded four studies where reference test was unclear/not reported 22 31–33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been limited studies assessing the utility of patient-administered vaginal swabs for STI testing in the ED; however, some studies have shown comparable or even higher sensitivities from using intravaginal swabs compared to endocervical swabs. 6,7,9 Allowing an asymptomatic patient to collect her own vaginal swab for STI testing limits the demands on resources and personnel in the ED, since a traditional pelvic exam can be time and resource intensive. Performing a pelvic exam often requires moving the patient to a pelvic exam room, cleaning an additional room, finding a chaperone for the patient, and adding time to the clinician's workload.…”
Section: Discussionmentioning
confidence: 99%
“…8 One small previous study demonstrated that patient self-collected vaginal swabs were not inferior for detecting C. trachomatis and N. gonorrhoeae in a single ED. 9 The use of vaginal swabs for STI testing in the ED provides an option for a patient-collected sample in appropriate situations. This can reduce the need for the more invasive procedure of a pelvic exam, saving time and resources, and perhaps promoting patient autonomy and reducing patient stress.…”
Section: Importancementioning
confidence: 99%